Фиксирующие манипуляторы для автоматизированной механической руки ассистента хирурга - Любчик, Михаил Абрамович; Ольштынский, В. А. (Харьковский политехнический институт, 1993)
The new type of the fixing preliminary oriented electromagnetic manipulator is proposed. The manipulator support reliable instrument griping during surgical operations in ststionary and field conditions.
Fixing manipulators for automated mechanical surgeon assistant arm
Keywords: хирургические операции; роботы; точность; операторы